Inhibition of Cancer Cell Migration by Gold Nanorods: Molecular Mechanisms and Implications for Cancer Therapy. (5th September 2014) - Zhou, Teng; Yu, Meifang; Zhang, Bo; Wang, Liming; Wu, Xiaochun; Zhou, Hejiang; Du, Yipeng; Hao, Junfeng; Tu, Yaping; Chen, Chunying; Wei, Taotao
<x xml:space="preserve">Abstract</x> Gold nanorods have received much attention because of their distinct physicochemical properties and promising applications in bioimaging, biosensing, drug delivery, photothermal therapy, and optoelectronic devices. However, little is known regarding their effect on tumor metastasis. In the present investigation, serum protein‐coated gold nanorods (AuNRs) at low concentrations is shown to exhibit no apparent effects on the viability and proliferation of three different metastatic cancer cell lines, that is, MDA‐MB‐231 human breast cancer cells, PC3 human prostate cancer cells, and B16F10 mouse melanoma cells, but effectively inhibit their migration and invasion in vitro. Quantitative proteomics and real‐time PCR array analyses indicate that exposure of cells to AuNRs can down‐regulate the expression of diverse energy generation‐related genes, which accounts for their inhibition of mitochondrial oxidative phosphorylation (OXPHOS) and glycolysis. The impairment of OXPHOS and glycolysis results in a distinctive reduction of ATP production and subsequent inhibition of F‐actin cytoskeletal assembly, which is crucial for the migration and invasion of cancer cells. The inhibitory effect of AuNRs on cancer cell migration is also confirmed in vivo. Taken together, the unique mechanism in inhibiting cancer cell migration by AuNRs might provide a new approach to specific cancer therapeutic treatment.